(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper describes an experimental study on the frequency characteristics of an electropneumatic tracking system with a high-speed pneumatic on/off valve (HSPV) and Pulse Width Modulation (PWM) control. A demonstration experimental test bench has been developed to analyze the Bode diagrams of magnitude and phase for an electropneumatic tracking system with a double-rod pneumatic cylinder, and the system's critical frequency has been determined. A specialized virtual instrument is used for control and data acquisition. The process control and data processing are performed automatically by a computer and the corresponding NI interface board. The results are presented in graphical form and analysis of the obtained Bode Diagrams was made.